Agency and Bandura’s Model of Triadic Reciprocal Causation: An Exploratory Mobility Study Among Metrorail Commuters in the Western Cape, South Africa - Bergman, Zinette; Bergman, Manfred Max; Thatcher, Andrew (Frontiers in Psychology, 2019)
Most studies on sustainable mobility focus on technological, socio-structural, or psychosocial influences, while neglecting individual motivations and practices. In this study, we examine mobility motivations and practices as part of a complex interplay between psychosocial and socio-structural dimensions within the mobility infrastructure of Metrorail in the Western Cape. Drawing on Albert Bandura’s theory of personal agency and the model of triadic reciprocal causation, we interviewed 38 (mean age 33 years, SD 11, 50% women/men) commuters and analyzed the data using Hermeneutic Content Analysis and multidimensional scaling. Based on our analyses, we identified three pathways that describe the mobility practices of Metrorail users, each with its own purpose and function. We explored these pathways and their consequences for sustainable mobility in relation to daily commuter agency, motivations, and past experiences.